Information System for Wet Garbage Bin Data Management in Local Areas: A Case Study of Langu Subdistrict Administrative Organization, Satun Province - Sakphet, Norathep; Jitrugtham, Chatirot; Bunjan, Annop; Yingdumnoon, Kullaphat; Rodklai, Sakan; Pumpuang, Chanyanuch (Journal of Applied Informatics and Technology, 2025)
This research focuses on developing an information system for managing wet garbage bin data in the Langu Subdistrict Administrative Organization, Satun Province. The aim is to resolve disorganized wet garbage bin management and enhance the efficiency of local waste data administration. The research methodology consists of three key phases: analyzing system requirements, developing the system using Flutter Framework technology, and evaluating user satisfaction. Experimental results show that the developed system effectively reduces issues related to wet waste in the area, mitigates environmental impacts, and fosters greater community participation in waste management efforts. Furthermore, integrating the findings with relevant theories and previous studies underscores the critical role of innovation and modern technology in establishing sustainable local waste management solutions.